2020
DOI: 10.1002/app.50382
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fiber orientation, temperature and relative humidity on the long‐term performance of short glass fiber reinforced polyamide 6

Abstract: As a result of processing of short fiber reinforced thermoplastics, the fiber orientation varies throughout a product giving rise to a pronounced anisotropic mechanical response. Different flow conditions in a product result in spatial variation in both short‐ and long‐term mechanical properties. In this study, a modeling approach is presented to evaluate the lifetime of short fiber reinforced polyamide 6, both in plasticity‐ and crack growth controlled regions of failure. In the plasticity‐controlled region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…Similar conclusions can be drawn from the results of some other researchers. [18,30] In addition, the effect of plaque thickness on fiber orientation and product strength was studied. Figure 7 shows the comparison of simulation and experimental results.…”
Section: Fiber Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conclusions can be drawn from the results of some other researchers. [18,30] In addition, the effect of plaque thickness on fiber orientation and product strength was studied. Figure 7 shows the comparison of simulation and experimental results.…”
Section: Fiber Orientationmentioning
confidence: 99%
“…Existing studies are more inclined to verify the relationship between weld line, fiber orientation and mechanical properties through lots of experiments. [4,[14][15][16][17][18] However, in practice production, optimizing fiber orientation and weld lines through experiments can greatly increase production costs, especially for expensive special engineering polymers such as Polyether ether ketone (PEEK). Therefore, it is of vital importance to analyze the geometric dimensions, mold design, process conditions, and so on through simulation in the design stage to improve the mechanical properties of the products.…”
Section: Introductionmentioning
confidence: 99%
“…Among thermoplastic polymers, polyamides have received great attention thanks to their unique merit like superior characteristics at elevated temperatures. 27 Polyamide 6 (PA6) with favorable strength, ductility 28 as well as cost-effectiveness, 29 and polyamide 6,6 (PA66) with high mechanical performance 30 and applications in a wide temperature range 31 are of enormous interest by various engineering fields. It is well known that glass fiber (GF) is one of the most popular reinforcing materials for polyamide matrix 32,33 and injection molding is excellent for the fabrication of fiber reinforced thermoplastics due to its performance and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a recent study in our group, however, have opened a new, promising possibility to directly link fiber orientation to the anisotropic time-dependent response [12,13]. In an extensive experimental effort, it was demonstrated that the rate-dependent, anisotropic (yield) strength of short and long fiber-reinforced thermoplastics generally displays a multiplicative decoupling of the effects of strain rate and loading angle [12,13]. Additionally, it was shown that, at a fixed strain rate, the yield strength appears to be uniquely coupled to the average fiber orientation in the direction of testing [14].…”
Section: Introductionmentioning
confidence: 99%